Google Trends (GT) related to influenza - Wiwanitkit, Viroj (2015)
The recent paper on Using Google Trends (GT) to Estimate the Incidence of Influenza-Like Illness in Argentina 1 is very interesting. Orellano et al. studied Google Flu Trends (GFT) and GT with a conclusion regarding “the utility of GT to complement influenza surveillance”. Indeed, the usefulness of GFT and GT has been mentioned in some earlier reports 2,3. However, as a computational model, there are several things to be considered in the simulation 4. Under- or over-estimation can be expected and this is still the present problem in using the Google system for predicting influenza 4. There is a need for modifications of GT and GFT into a more specific tool that is appropriate for each context. A good example of this is the development of FluBreaks by Pervaiz et al.